A modified rigid-body-spring method for modeling damage and failure of brittle rocks subjected to triaxial compression. (December 2022) - Yao, Chi; He, Chen; Jiang, Qinghui; Shao, Jianfu; Zhou, Chuangbing
Abstract: A three-dimensional modified rigid-body-spring method (3D mRBSM) is presented to simulate the progressive damage and failure process of rocks under triaxial compressive conditions. Different from the original RBSM model, the mRBSM employs spring-set groups distributed on interfaces between blocks to approximately describe the progressive failure process of micro-cracks without increasing the size of governing equations. Firstly, the basic equations of 3D mRBSM are derived. A new randomly distributed Voronoi-based mesh technique is proposed to reproduce homogeneous and isotropic rock materials. Then, relationships between macro and micro elastic parameters are established, and a calibration procedure for parameters of failure criterion is adopted based on the trial-and-error procedure. Lastly, the new model is applied to simulate pseudo triaxial and true triaxial compression tests on brittle rocks. Results show that the proposed model correctly captures common mechanical properties of brittle rocks, such as nonlinear stress–strain relationship, brittle-ductile transition, confining pressure dependence of failure mode and medium principal stress effect. The above research demonstrates that the mRBSM is successfully upgraded to three-dimensional version. The new method is a promising tool for simulation of deformation and failure process of rocks under true triaxial stress conditions.